Causes, Symptoms, Classification and Treatment of Neurosis - Ashotovich, Abramian Gevork; Igorevich, Avramenko Vladislav; Alievich, Aliev Shamil; Alexeevna, Filippova Yulia (International Journal of Psychosocial Rehabilitation, 2020)
According to statistics, about 70% of the population in Russia suffers from neurosis. This disease has four forms, each of which proceeds differently: neurasthenia, anxiety and phobic disorders, obsessive- compulsive neurosis, and hysterical neurosis. The neurosis itself can be described as a stagnant disorder that cannot let go of a person for years and decades due to the fixation of the psyche on some point in the patient's life, internal or intrapsychic conflict or not fully processed psychotrauma (and not rarely it is not even remembered by the patient because it becomes driven into the dark depths of the unconscious). The most difficult task in the diagnosis of neuroses is its classification and especially differentiation from symptomatically similar conditions of a different nature (schizophrenia, psychopathy, etc.). Experimental psychological examinations become very informative, and instrumental methods of examination (MRI, CT, etc.) are prescribed to exclude a tumor or infection of the Central nervous system. This article is a study of a patient with a neurosis of the type of anxiety and phobic disorders. During the examination, the patient was recommended a certain treatment regimen, the results of which are also presented in this article.